Embolia cutis medicamentosa pós-injeção – Síndrome de Nicolau: Relato de caso e revisão de literatura - Chagas, Carlos Alberto Araujo; Leite, Tulio Fabiano de Oliveira [UNESP]; Pires, Lucas Alves Sarmento (FapUNIFESP (SciELO), 2016)
We report on the case of a 40-year-old male who was admitted to the clinic with a large ulcer on his left buttock, 3 days after an intramuscular benzathine penicillin injection. The patient was diagnosed with Nicolau syndrome, a rare vascular complication in which a lesion develops after intramuscular injection. Symptoms are intense pain at the injection site, erythema, and livedoid dermatitis, which leads to necrosis of skin, subcutaneous tissue and muscle tissue. It was described by Nicolau after intramuscular injections of bismuth salt for syphillis therapy. Nicolau syndrome is rare, but its symptoms are devastating and healthcare professionals must be aware of this clinical entity, since intramuscular injections are common procedures for administration of drugs.
Post-injection embolia cutis medicamentosa – Nicolau syndrome: Case report and literature review
Keywords: Injections; Intramuscular; Nicolau syndrome; Ulcer